A model of particle removal in a dissolved air flotation tank: Importance of stratified flow and bubble size. (1st January 2015) - Lakghomi, B.; Lawryshyn, Y.; Hofmann, R.
Abstract: An analytical model and a computational fluid dynamic model of particle removal in dissolved air flotation were developed that included the effects of stratified flow and bubble-particle clustering. The models were applied to study the effect of operating conditions and formation of stratified flow on particle removal. Both modeling approaches demonstrated that the presence of stratified flow enhanced particle removal in the tank. A higher air fraction was shown to be needed at higher loading rates to achieve the same removal efficiency. The model predictions showed that an optimum bubble size was present that increased with an increase in particle size. Graphical abstract: Highlights: Analytical and CFD models of particle removal in a DAF system were developed. Stratified flow was shown to enhance particle removal efficiency. Higher air fractions were required at higher loading rates. An optimum bubble size was present that depended on the particle size.